Text VS Discourse: Reformulating the Definition, Integrating Different Perceptions - Muhammad Zainal Muttaqien; Roma Ulinnuha; Rina Heriyanti (Fakultas Komunikasi, Sastra, dan Bahasa, 2024)
There have long been different perceptions on what text and discourse are. Some experts in linguistics view these two objects as the same thing whereas others see them as two different forms. Occasionally, text and discourse are parallel to each other but often the former is seen as the subordinate of the latter and vice versa. This paper aimed at formulating new definitions of text and discourse in order to clarify the nature of each as well as the relations that may exist between them. The method applied in this study was by collecting as many as definitions of text and discourse as stated by linguistic experts and quoted in references. These data were then compared and contrasted to find out the similarities and the differences between the objects for drawing a conclusion in the form of definitions and descriptions that precisely represent the characteristics of each. The result shows that, text and discourse share both similarities and differences. At certain level, they can be seen as the same entity but in other conditions one may take position as part of the other.